2022
DOI: 10.1111/nuf.12765
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' professional image in the Covid‐19 pandemic in Turkey: A cross‐sectional study

Abstract: Background Nursing students' professional perceptions are affected by the environment they live in. Nursing students think that the nursing profession is important during the pandemic. Purpose This descriptive, cross‐sectional study was conducted to determine the nursing students' professional image perceptions and the affecting factors during the Covid‐19 pandemic in Turkey. Methods The research population consisted of all nursing students (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Furthermore, the problems of nursing students with stress, anxiety, and depression were different in different research in different countries. Dastan and colleagues performed research on the mental health of nursing students in Turkey in 2021 (38.2% with Stress, 58.8% with Anxiety, and 56.3% with Depression) (Dastan et al, 2021), Rasmussen and coworkers carried out research on the mental health of Australian nursing students in 2021 (55% with Stress, 52.7% with Anxiety, and 63.8% with Depression) (Rasmussen et al, 2021), which were higher ratio than in this current study. Otherwise, the prevalence of nursing students who had problems with stress, anxiety, and depression in this research was higher than that of Juan Gao report which was conducted from 12–13 April 2020 in China (Gao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the problems of nursing students with stress, anxiety, and depression were different in different research in different countries. Dastan and colleagues performed research on the mental health of nursing students in Turkey in 2021 (38.2% with Stress, 58.8% with Anxiety, and 56.3% with Depression) (Dastan et al, 2021), Rasmussen and coworkers carried out research on the mental health of Australian nursing students in 2021 (55% with Stress, 52.7% with Anxiety, and 63.8% with Depression) (Rasmussen et al, 2021), which were higher ratio than in this current study. Otherwise, the prevalence of nursing students who had problems with stress, anxiety, and depression in this research was higher than that of Juan Gao report which was conducted from 12–13 April 2020 in China (Gao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies on the image of nursing in society, there are limited studies conducted specifically during the Covid‐19 pandemic. Most of the studies on society's perception of nursing have been conducted with nurses and nursing students 21,22 . There is no study conducted on society's perception of nursing during the Covid‐19 pandemic period in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Turkey revealed that nurses are seen as people who perform care services and assist physicians, but they are also evaluated as qualified and have good communication skills 6 . Some studies, although the image of nursing is not very good, it states that it is perceived at a moderate 26 or good level 21,22 . The image of nursing held by society is at odds with the definition of nursing set forth in a law enacted in Turkey in 2011; according to this law, nursing is defined as a profession with areas of expertize 27…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations